EFEKTIFITAS METODE AL-BAYAN UNTUK MENINGKATKAN KEMAMPUAN MEMBACA HURUF HIJAIYAH BAGI ANAK TUNARUNGU - Heni Herlina, Martias, Z, Ganda Sumekar (Jurnal Penelitian Pendidikan Khusus, 2013)
This study originated from a case study conducted by the author in SLB Negeri 1 Padang. Researcher found deaf child in the sixth grade who can not read some letters Hijaiyah. In this study the author limit letters of Hijaiyah in ج to ص using Al-Bayan method to improve the ability to read a few letters Hijaiyah for deaf children. This type of research is Single Subject Research (SSR) with ABA design. The data obtained were processed with graphics, so the results can be drawn between the conditions. The result is Al-Bayan method can improve the ability in reading my letters Hijaiyah for deaf children (x).